SENSOR AND ACTUATOR INFRASTRUCTURE FOR DEMAND-CONTROLLED VENTILATION AND INDOOR AIR QUALITY MANAGEMENT IN AN AUTOMATED HVAC SYSTEM (Ustozlar uchun, 2026)
This article presents a scientific analysis of the sensor and actuator infrastructure required for demand-controlled ventilation (DCV) and indoor air quality (IAQ) management in an automated HVAC system. Problem: fixed ventilation rates, independent of zone occupancy, cause either energy waste in unoccupied zones or inadequate ventilation in occupied zones (CO₂ exceeding 1400 ppm), both common in conventional administrative building HVAC systems. Method: a zone-level sensor system was designed based on the Siemens QPA2062 NDIR CO₂ sensor, QAA2281 temperature/humidity sensor, PIR motion sensors, and Belimo TSV24-SR VAV actuators; real-time occupancy is estimated from a CO₂ mass-balance model. Result: the sensor system estimated occupancy with ±1 person accuracy and maintained CO₂ at 940 ppm (down from 1420 ppm under fixed ventilation). Conclusion: the DCV algorithm saved 18,600 kWh (16.3%) of annual ventilation energy, with sensor signal reliability of 98.4%.